IMPLEMENTASI PENGGUNAAN COLD PACK DALAM MENGURANGI NYERI PADA PASIEN POST SECTIO CAESAREA DI RSUD CILACAP: THE USE OF COLD PACKS TO RELIEVE PAIN IN PATIENTS FOLLOWING A CAESAREAN SECTION AT CILACAP GENERAL HOSPITAL - Dinda Cetrin Erike; Tophan Heri Wibowo; Madyo Maryoto (LPPM Universitas Abdurrab, 2026)
Pain is the primary complaint among patients following a cesarean section and can hinder the recovery process. One type of non-pharmacological therapy that may be used to help reduce pain is cold pack therapy. This therapy works by applying a cooling effect to the surgical wound area, thereby helping to reduce inflammation and pain intensity. Furthermore, postoperative pain management remains suboptimal, and the use of analgesics carries side effects; additionally, based on a preliminary survey at Cilacap Regional General Hospital, there has been no specific implementation of cold pack therapy. The objective of this Community Service activity is to determine the effectiveness of implementing cold pack therapy in reducing pain levels among patients following cesarean section surgery at Cilacap Regional General Hospital. The method used involved measuring pain levels using the Numeric Rating Scale (NRS) before and after cold pack application. The study included 30 participants. The results showed a reduction in pain levels after cold pack therapy was administered, with the majority of participants experiencing a decrease from moderate to mild pain. Conclusion: Cold pack therapy is effective as a complementary non-pharmacological intervention in reducing pain in patients following cesarean section surgery.